2007
DOI: 10.1063/1.2766856
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms behind blue, green, and red photoluminescence emissions in CaWO4 and CaMoO4 powders

Abstract: A combined experimental and theoretical study was conducted to analyze the photoluminescence (PL) properties of ordered and disordered CaWO4 (CW) and CaMoO4 (CM) powders. Two mechanisms were found to be responsible for photoluminescence emission in CW and CM powders. The first one, in the disordered powders, was caused by oxygen complex vacancies [MO3∙VOx], [MO3∙VO•] and [MO3∙VO••], where M=W or Mo, which leads to additional levels in the band gap. The second mechanism, in ordered powders, was caused by an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 13 publications
5
79
0
5
Order By: Relevance
“…), and external T-(B g , E g , E g ) modes that are in agreement with the results reported by Campos et al 69 and Hazen et al 98 Table III reports normal vibrational modes active in Raman for s and s* states and experimental results. The small shifts observed on the positions of Raman modes can arise from different factors, such as: preparation methods, average crystal size, interaction forces between the ions or the degree of structural order in the lattice.…”
Section: Ft-raman Spectroscopy Analysessupporting
confidence: 82%
See 2 more Smart Citations
“…), and external T-(B g , E g , E g ) modes that are in agreement with the results reported by Campos et al 69 and Hazen et al 98 Table III reports normal vibrational modes active in Raman for s and s* states and experimental results. The small shifts observed on the positions of Raman modes can arise from different factors, such as: preparation methods, average crystal size, interaction forces between the ions or the degree of structural order in the lattice.…”
Section: Ft-raman Spectroscopy Analysessupporting
confidence: 82%
“…This emission was quite different from previous results of crystalline CaWO 4 powders synthesized by the polymeric precursor method were the PL emission has a maximum centered at 520 nm, the green area of visible spectra. 69,104 Both CaWO 4 crystals, obtained by processing in MH system and polymeric precursor method, were crystalline at long range order in agreement with XRD analyses. However, the difference in the maximum PL emission between the samples obtained by the two methods show that there are structural differences between them.…”
Section: -7mentioning
confidence: 49%
See 1 more Smart Citation
“…The spectra show a violet-blue emission band in range of ~370-450 nm. This is similar with the blue-green luminescence reported for MeWO 4 powders in previous literature (Thongtem et al, 2008;Campos et al, 2007;Shen et al, 2011;Li et al, 2014). Figure 5 shows the luminescence spectra of Sm 3+ in the phosphors under monitoring emission at 643 nm and excitation at 404 nm.…”
Section: Resultssupporting
confidence: 79%
“…12,13 As a result of previous studies of photoluminescence (PL) properties, we recently reported that two mechanisms were found to be responsible for PL emission in CaWO 4 and CM powders. 14 The first mechanism, in the disordered powders, was caused by oxygen complex vacancies [MO 3 In this work, a theoretical approach was given to the experimental PL results of the green-light emission of CM. Three disorder-type simulations were made in the crystalline (ordered) tetragonal unit cell as follows: in the network former (Mo), in the network modifier (Ca), and in the network former-modifier (Mo/Ca).…”
Section: Introductionmentioning
confidence: 99%